Basic concepts for teaching developmentally disabled and mentally retarded people - Monaco, Greg; Smith, Jim (Topeka, Kansas : Monaco-Beck Inc., 1989)
Provides a list of concepts and techniques for teacher of the handicapped in their daily work of caring, teaching and dealing with them
8 videocassettes (VHS) (113 mins.)
Photographs courtesy of The Archive Division of The Menninger Foundation
Copy available in DVD format
Keywords: Teaching -- United States; Special education -- United States; Handicapped -- Education